Pegegog 2023
DOI: 10.47750/pegegog.13.04.23
|View full text |Cite
|
Sign up to set email alerts
|

E-Leadership, Technology Acceptance and Technological Self-Efficacy: Its Effect on Teacher Attitudes in Using Virtual Learning Environments

Abstract: This study seeks to understand better how e-leadership, technology acceptance and technological self-efficacy contribute to improved teacher attitudes in using virtual learning environments. The method used was quantitative with structural equation modeling with SmartPLS 3.2.8. The population of this study consisted of 1,570 teachers in the Malang district, Indonesia. A sample of 420 teachers was selected using a systematic random sampling technique. The findings demonstrated a positive and significant effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The evaluation of the principal's technology leadership in this study adhered to the five recent standards outlined by the International Society for Technology in Education for Administrators [16]. Widely employed in research studies, these standards have been used to gauge their impact on teachers' ICT integration capabilities or, more broadly, teachers' digital competencies (as evident in prior studies [6,9,30,34,44,95,101] and in the context of learning organizations as integral to school culture [120]. To assess this, teachers were required to evaluate the extent to which the principal, as a technology leader, embodied the five dimensions of the ISTE-A standard: equity and citizenship advocate, visionary planner, empowering leader, systems designer, and connected learner.…”
Section: Principal Technology Leadershipmentioning
confidence: 99%
See 3 more Smart Citations
“…The evaluation of the principal's technology leadership in this study adhered to the five recent standards outlined by the International Society for Technology in Education for Administrators [16]. Widely employed in research studies, these standards have been used to gauge their impact on teachers' ICT integration capabilities or, more broadly, teachers' digital competencies (as evident in prior studies [6,9,30,34,44,95,101] and in the context of learning organizations as integral to school culture [120]. To assess this, teachers were required to evaluate the extent to which the principal, as a technology leader, embodied the five dimensions of the ISTE-A standard: equity and citizenship advocate, visionary planner, empowering leader, systems designer, and connected learner.…”
Section: Principal Technology Leadershipmentioning
confidence: 99%
“…This aligns with the findings of Aktaş and Karaca [127], who found that technology leadership influences the technological skills of school administrators, particularly their self-efficacy (defined as ATU) in using technology tools. Likewise, Purnomo et al [9] discovered the influence of principals' technology leadership, such as empowering leaders, wherein it enhances teacher acceptance, self-efficacy, and attitude in incorporating technology into the learning environment. Furthermore, the existing studies consistently show how principal technology leadership contributes to teacher technology incorporation skills in the teaching process [11,18,44,120,128].…”
Section: Direct Effectmentioning
confidence: 99%
See 2 more Smart Citations